PENGARUH LUAS LAHAN DAN PELATIHAN TERHADAP PRODUKSI DAN PENDAPATAN PETANI KAKAO DI DESA YEHEMBANG KAUH KECAMATAN MENDOYO KABUPATEN JEMBRANA - Ardana, I Gede Angga Putra; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
This study aims to analyze the influence of land area and training on cocoa farmers' production and income. This research was conducted in the village of Yehembang Kauh, Mendoyo District, Jembrana Regency. The number of samples taken was 90 farmers, using the proportional random sampling method. Data collection is done through interviews and observations. The analysis technique used is path analysis. Based on the results of the study showed that the area of ??land and training had a positive and significant effect on the production of cocoa farmers in the Village of Yehembang Kauh, Mendoyo District, Jembrana Regency. The results of the analysis of the area of ??land, training, and production have a positive and significant effect on the income of cocoa farmers in Yehembang Kauh Village, Mendoyo District, Jembrana Regency. Farmer production mediates the influence of land area and training on cocoa farmers' income in Yehembang Kauh Village, Mendoyo District, Jembrana Regency. Keywords: land area, training, production, income